2023
DOI: 10.1038/s41598-023-28899-0
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization analyses of associations between breast cancer and bone mineral density

Abstract: The purpose of this study was to verify whether there is a causal relationship between breast cancer and bone mineral density (BMD). Summary statistics for exposures and outcomes were obtained from corresponding genome-wide association studies. The bidirectional and multivariate mediated Mendelian randomization (MR) analyses were performed. In the bidirectional MR analysis, breast cancer might reduce the BMD of the heel (HE-BMD) (FDR = 1.51 × 10−4) as might its ER+ subtype (FDR = 1.51 × 10−4). From BMD to brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The weighted median approach was employed in instances where the MR analysis was influenced by a significant proportion of invalid instrumental variables contributing to half of the analysis weight [ 27 ]. We calculated F-statistics using the approximation method introduced by HongWu et al [ 28 ]. We defined IVs with F-statistics exceeding a threshold of 10 as valid for our analysis, ensuring a strong first-stage regression.…”
Section: Methodsmentioning
confidence: 99%
“…The weighted median approach was employed in instances where the MR analysis was influenced by a significant proportion of invalid instrumental variables contributing to half of the analysis weight [ 27 ]. We calculated F-statistics using the approximation method introduced by HongWu et al [ 28 ]. We defined IVs with F-statistics exceeding a threshold of 10 as valid for our analysis, ensuring a strong first-stage regression.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, these observational studies cannot explain the causal relationship between the two. A Mendelian randomization study by Wu et al [15], based on individuals of European descent, suggested that BMD is not the risk factor for BC,rather ,BC can lead to decreased bone density. Most of the observational studies collected on the BMD and the risk of BC are based on European or Caucasian populations, while the incidence and mortality rates of BC vary signi cantly in different regions of the world [16].…”
Section: Introductionmentioning
confidence: 99%